Gender Discourses within Pesantren in Cirebon: Understanding the Typologies of Kyais’ Interpretations of the Concept of Qawwām - Nuroniyah, Wardah (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
The gender discourse within pesantren is a significant scientific subject due to its reliance on classical fiqh literature that often maintains patriarchal ideology. One such issue is the interpretation of the concept of “qawwām”, a fragment of the Qur’anic verse (An-Nisā’: 34), meaning supporter or protector, in which the kyai (the spiritual leaders of pesantren) predominantly associates the role with men and their responsibilities. This understanding is influenced by the traditional (salaf) paradigm and results in a patriarchal interpretation. This study applies descriptive qualitative analysis to answer how pesantren leaders interpret the concept of “qawwām” in relation to gender ideology. Data was conducted through interviews with kyais in Cirebon and observations of their family life. The article analyses their understanding of “qawwām” based on the trichotomy of gender understanding: extreme patriarchy, moderate patriarchy, and liberal. The article argues that differences in the kyais’ viewpoints regarding the distribution of roles within the family can be traced back to their textual, eclectic, and contextual comprehension of religious teachings. The study recommends that an intricate understanding of religious teachings, taking into account the evolving social context and the diverse range of interpretations, may pave the way for a more balanced and egalitarian allocation of responsibilities between spouses in the family.